Tinjauan Mendalam Terhadap Peran Logika Dalam Pemikiran Dan Penalaran Manusia - Melkisedek Melkisedek; Nur Lestari; Dedi Dedi; Moses Lawalata (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Logic is an important foundation in human thinking and reasoning. In this review, we will examine the role of logic in the context of human thought, both in everyday life and in scientific disciplines. We begin by discussing the introduction of the concept of logic and the history of the development of logic in identifying its fundamental role in facilitating rational and systematic thought processes.Then we will analyze how logic influences various aspects of human life, from individual decision making to the development of science and technology. We also explore how the use of logic can improve human reasoning, reduce bias, and increase the clarity and precision of arguments. In addition, we discuss the challenges associated with applying logic in complex social and cultural contexts. We investigate how factors such as emotions, beliefs, and cultural background influence humans' ability to use logic effectively.Finally, we conclude by underlining the importance of understanding the role of logic in human thinking and reasoning to develop better critical thinking skills and promote the effective use of logic in various aspects of human life.